Coeliac Disease Pathogenesis: The Uncertainties of a Well-Known Immune Mediated Disorder - Dunne, Margaret R.; Byrne, Greg; Chirdo, Fernando G.; Feighery, Conleth (Frontiers in Immunology, 2020)
Coeliac disease (CD) is a common small bowel enteropathy arising in genetically predisposed individuals and caused by ingestion of gluten in the diet. Great advances have been made in understanding the role of the adaptive immune system in response to gluten peptides. It is now established that these peptides bind in a specific manner to certain MHC class II molecules with the resultant activation of lamina propria T helper (TH) cells. Peptide modification by the enzyme tissue transglutaminase (TG2) enhances this event. Activated TH cells are then considered to promote intra-epithelial lymphocyte (IEL) cytolysis of enterocytes, although amongst this highly varied populations of cells, some IELs may play a local immune regulatory role. Despite detailed knowledge of these immune mechanisms, the complete series of pathogenic events responsible for development of the tissue lesion remains less certain. In addition to gluten peptides which stimulate TH cells, it has been suggested that other peptides could directly interact with the intestinal mucosa, contributing to disease pathogenesis. Interleukin (IL)-15 produced by intestinal epithelial cells and local antigen presenting cells is a pivotal event in the disease process. Activation of eosinophils, mast cells and neutrophils in the coeliac lesion has been described and may contribute to the disease process. Myofibroblasts, a major source of TG2 and metalloproteases, may play a central role in intestinal tissue remodelling. In this complex disorder, much of the heritable risk has yet to be defined and future findings may shed light on other pathways involved in disease pathogenesis. The study of CD continues to be instructive in our understanding of chronic immune-mediated diseases.